2014
DOI: 10.4161/gmic.29796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of commensals and probiotics on visceral sensitivity and pain in irritable bowel syndrome

Abstract: The last ten years' wide progress in the gut microbiota phylogenetic and functional characterization has been made evidencing dysbiosis in several gastrointestinal diseases including inflammatory bowel diseases and irritable bowel syndrome (IBS). IBS is a functional gut disease with high prevalence and negative impact on patient's quality of life characterized mainly by visceral pain and/or discomfort, representing a good paradigm of chronic gut hypersensitivity. The IBS features are strongly regulated by bidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 83 publications
(103 reference statements)
2
35
0
3
Order By: Relevance
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
See 1 more Smart Citation
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…In addition, both probiotic and antibiotic treatments have been shown to have positive effects on pain symptoms in clinical studies of IBS patients. [127] …”
Section: Microbial Signals Modulate Visceral Painmentioning
confidence: 99%
“…This strain was also shown to increase MOR expression in humans [28]. It is also well known that probiotics enhance intestinal barrier function and that by reducing hyperpermeability, probiotics decrease visceral hypersensitivity, the effect being strain specific [29]. For instance, Lactobacillus farciminis was observed to prevent stress-induced hyperpermeability and hypersensitivity through a decrease of the myosin light chain phosphorylation, responsible for epithelial cells cytoskeleton contraction and subsequent tight junction opening [30].…”
Section: Discussionmentioning
confidence: 96%
“…Повышенная концентрация про-теаз была обнаружена в образцах фекалий пациентов с синдромом раздраженного кишечника, вызванным определенными видами микроорганизмов, живущих в кишечнике [44,45]. Предполагается, что аномальная микробиота активирует иммунные реакции слизистой оболочки, которые повышают проницаемость эпителия, активируют ноцицептивные сенсорные пути, индуцирую-щие висцеральную боль, и приводят к нарушению работы энтеральной нервной системы [46,47].…”
Section: влияние микробиоты на состояние мукозального иммунитетаunclassified